Overcoming Insecurity in Competing for Jobs in the Pandemic Era - Danny Sanjaya Arfensia; Atika Dian Ariana; Danu Aji Nugroho; Ichwan Cahyono; Nadhira Inastiti Raharjo; Khoirunnisa Khoirunnisa; Riris Ristiana; Nono Hery Yoenanto; Rudi Cahyono (Faculty of Psychology, Universitas Gadjah Mada, 2021)
Limited job opportunities amidst high competition in job-seeking during the pandemic can create a sense of insecurity in competing for jobs. This study aimed to help individual overcome feelings of insecurity and increase confidence in competing for jobs in the pandemic era. The study used a psychoeducation program to improve Optimism and Confidence with Appreciative Inquiry approach. The intervention was held in virtual space, through a webinar that was attended by 33 participants. The data collection technique used a sampling technique. Data analysis was carried out using paired sample t-test. The result showed that there was a significant difference in the Optimistic dimension (t=2.528; p=0.020) and there was a significant trend in the Confidence variable (t=1.930; p=0.068). Psychoeducation with the application of the online learning model and Appreciative Inquiry approach can increase individual confidence, especially in the aspect of optimism.